L’endettement international et les problèmes d’ajustement : une perspective générale - Tremblay, Rodrigue (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
This paper reviews the theory of international indebtedness over time from the viewpoint of both the demand and the supply of international credit. The demand for foreign credit depends ultimately on the optimal trade-off between financing and correcting external deficits, subject to the constraint of availability of credit. The conditions for debt crises to arise are analysed. The overall supply of international credit depends mainly on trade imbalances and on the rate of growth of international reserves. The supply of credit for a single country depends on risk indicators related to its solvency and liquidity positions.It is assumed that the international cycle of indebtedness for balance of payments reasons has a deflationary potential once borrowing limits have been reached.